Thực trạng phát triển năng lực điều chỉnh cảm xúc cho trẻ 5-6 tuổi qua trải nghiệm ở một số trường mầm non trên địa bàn tỉnh Tuyên Quang - Nguyễn, Thị Vui; Vũ, Thị Kiều Trang (Tạp chí Giáo dục, 2025)
Developing emotional regulation abilities for 5-6 years old children is one of the important educational objectives in kindergartens, helping children recognize and regulate their own emotions, develop basic social skills, and prepare for elementary school. However, in practice, many teachers face difficulties when implementing effective methods and organizational forms to develop emotional regulation abilities in children. This study shows that teachers have a correct understanding of the important role of experiences in developing emotional regulation abilities for children. Methods such as games, discussions, and role-playing are commonly used. However, the process of developing emotional regulation abilities has not been fully applied, with some steps like sharing, reflecting on experiences, and applying lessons learned not being carried out regularly. This article investigates the current state of developing emotional regulation competency for 5–6-year-old children through experiential activities in several preschools in Tuyen Quang province. The findings serve as a practical basis for proposing measures to enhance the development of emotional regulation abilities in 5–6-year-old children through experiential learning in preschools.